Digital-Based Physics Pocket Book Design with Short Counting Methods for Junior High School Students - Yanti, Fitri April; Kristiawan, Muhammad; Riastuti, Reny Dwi; Muthoharoh, Luluk; Noperi, Hendri (FKIP Universitas Lampung, 2022)
This study aims to design a digital-based physics pocket book with a short calculation method for junior high school students. This type of research and development is used in this study. At the design stage, we selected the ADDIE model. The design phase includes: the analysis phase, the stage design, the stage of development. Research data obtained by reviewing the curriculum, interviews, and validation questionnaires. Class VII, VIII, IX students, as many as 9 people, became the subject of a limited trial in this study. Data analysis was carried out by reviewing curriculum content, descriptive interview results, and quantitative analysis for validation. The results showed that the design of a digital-based physics pocket book with a short calculation method was valid and could be used by Junior high school students.Keywords: digital book, pocket book, short count method, physics learning.DOI: http://dx.doi.org/10.23960/jpmipa/v23i3.pp1030-1039